2018
DOI: 10.1002/ccd.27775
|View full text |Cite
|
Sign up to set email alerts
|

Radial hemostasis: Harder, better, faster, stronger?

Abstract: Key Points Hemostasis protocols after transradial catheterization are highly variable. Hemostatic patches potentially speed hemostasis at the arteriotomy site, improving efficiency and throughput. Larger trials of hemostatic patches are needed to demonstrate their superiority to conventional approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…It has also been shown that maintenance of antegrade radial flow during hemostasis (“patent hemostasis”) further reduces RAO 15‐17 . Greater duration and intensity of radial compression appear to increase RAO rates, however, there is no current standard for the length or technique of radial artery compression 18,19 . Informed, in part, by industry recommendations, compression time for diagnostic TRA procedures typically range from 90 to 120 min in the United States, but Asian centers routinely exceed 4–6 hr 18,19 Thus, further refinement of TRA hemostasis techniques remains a worthwhile endeavor.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that maintenance of antegrade radial flow during hemostasis (“patent hemostasis”) further reduces RAO 15‐17 . Greater duration and intensity of radial compression appear to increase RAO rates, however, there is no current standard for the length or technique of radial artery compression 18,19 . Informed, in part, by industry recommendations, compression time for diagnostic TRA procedures typically range from 90 to 120 min in the United States, but Asian centers routinely exceed 4–6 hr 18,19 Thus, further refinement of TRA hemostasis techniques remains a worthwhile endeavor.…”
Section: Introductionmentioning
confidence: 99%